Prevalence of self-medication practices in the Maharashtra population: a cross-sectional study - Kulkarni, Prerana P.; Madane, Tanvi S.; Kumbhar, Anjali (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Self-medication is a significant issue in public health, with varying global prevalence. It is one of the major causes of the emergence of antibiotic resistance in India. The study's objective was to identify the pattern, cause, and adverse events of self-medication in Maharashtra's urban and rural areas. Methods: A cross-sectional survey was conducted using a pre-populated questionnaire; including information on age (18-85 years), non-prescription and prescription medication use. Age, gender, past medical and medication history, social history, and self-medication pattern, frequency, reason, source of information, and adverse events noticed as a result of self-medication are all sociodemographic questions on the questionnaire. A percentage analysis was used to examine the data. Results: Study states that out of 400 sample, 76% of the individuals self-medicate, with painkillers (49.4%), antacids (23.7%), antibiotics (15.3%), being the most often used drugs for ailments like headache, fever, bodily pain, and acidity. The top most medications taken for self-medication are paracetamol (53.1%), pantoprazole (30.43%), ondansetron (13.62%), and azithromycin (12.46%); 66.07% usage of prescription drugs as self-medication was found. The most frequent causes of self-medication were discovered to be mild illnesses, the easy accessibility of medications, and chemist recommendations, 8% of those surveyed had adverse events, and sources of information were chemists, past prescriptions, family members, and acquaintances. Conclusions: In Maharashtra, self-medication is a prevalent practice that primarily utilizes over-the-counter (OTC) drugs. As a result, consumers should be made aware of the hazards of antibiotic resistance and other pharmaceuticals.